2016
DOI: 10.1002/ps.4324
|View full text |Cite
|
Sign up to set email alerts
|

RNAi as a management tool for the western corn rootworm, Diabrotica virgifera virgifera

Abstract: The western corn rootworm (WCR), Diabrotica virgifera virgifera, is the most important pest of corn in the US Corn Belt. Economic estimates indicate that costs of control and yield loss associated with WCR damage exceed $US 1 billion annually. Historically, corn rootworm management has been extremely difficult because of its ability to evolve resistance to both chemical insecticides and cultural control practices. Since 2003, the only novel commercialized developments in rootworm management have been transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 125 publications
1
74
0
6
Order By: Relevance
“…Transgenic plants engineered to express insect dsRNAs emerged as a potential technology after two independent groups proved the concept of applying RNAi to control agricultural insect pests (Baum et al, 2007; Mao et al, 2007). This approach has been developed to control lepidopteran, coleopteran and hemipteran agricultural pests (Katoch et al, 2013; Li et al, 2011; Paim et al, 2012), including Helicoverpa armigera in cotton (Mao et al, 2011; Mao et al, 2015; Qi et al, 2015; Chikate et al, 2016) and tobacco (Zhu et al, 2012; Xiong et al, 2013; Tian et al, 2015; Mamta, Reddy & Rajam, 2015), Diabrotica virgifera virgifera in maize (Baum et al, 2007; Fishilevich et al, 2016), Nilaparvata lugens in rice (Zha et al, 2011; Li et al, 2011; Yu et al, 2014; Qiu et al, 2016), Myzus persicae (Mao et al, 2015; Tzin et al, 2015) in Nicotiana benthamiana (Khan et al, 2013; Pitino et al, 2011) and Arabidopsis thaliana (Coleman, Pitino & Hogenhout, 2014; Li et al, 2015) and Sitobion avenae in wheat (Xu et al, 2014). However, the availability of methods that allow the screening and evaluation of candidate RNAi targets is a critical requisite for developing specific and efficient RNAi-based pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic plants engineered to express insect dsRNAs emerged as a potential technology after two independent groups proved the concept of applying RNAi to control agricultural insect pests (Baum et al, 2007; Mao et al, 2007). This approach has been developed to control lepidopteran, coleopteran and hemipteran agricultural pests (Katoch et al, 2013; Li et al, 2011; Paim et al, 2012), including Helicoverpa armigera in cotton (Mao et al, 2011; Mao et al, 2015; Qi et al, 2015; Chikate et al, 2016) and tobacco (Zhu et al, 2012; Xiong et al, 2013; Tian et al, 2015; Mamta, Reddy & Rajam, 2015), Diabrotica virgifera virgifera in maize (Baum et al, 2007; Fishilevich et al, 2016), Nilaparvata lugens in rice (Zha et al, 2011; Li et al, 2011; Yu et al, 2014; Qiu et al, 2016), Myzus persicae (Mao et al, 2015; Tzin et al, 2015) in Nicotiana benthamiana (Khan et al, 2013; Pitino et al, 2011) and Arabidopsis thaliana (Coleman, Pitino & Hogenhout, 2014; Li et al, 2015) and Sitobion avenae in wheat (Xu et al, 2014). However, the availability of methods that allow the screening and evaluation of candidate RNAi targets is a critical requisite for developing specific and efficient RNAi-based pest control.…”
Section: Introductionmentioning
confidence: 99%
“…37 If so, future studies on natural uptake of diet-derived sRNA should focus on invertebrates for which successful orally administered RNAi has been shown. For example, studies of diet-derived RNAi in the control of the corn rootworm 93 for agricultural uses has provided one of the best examples of natural uptake of dietary sRNAs. 37 Research in this area should focus on species for which genomic tools exist for both the plant species of the diet and the ingesting organism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, various toxins work by disrupting epithelial cells in the digestive tract, such as the pore forming peptide pesticides derived from Bacillus thuringiensis. 93 In addition, one group found that introduction of a cysteine protease that reduced the peritrophic matrix resulted in increased uptake of dsRNA delivered via transgenic plants to the bollworm, 94 indicating that non-cellular barriers are important for inhibiting sRNA uptake as well.…”
Section: Do Srnas Cross the Digestive Tract Barrier?mentioning
confidence: 99%
“…In Brazil, for example, studies demonstrated a high efficiency of the Bt soybean strain DAS-81419-2 (expressing two proteins) in the reduction of damage caused by A. gemmatalis, C. includens, H. virescens, and S. cosmioides during the vegetative and reproductive stages (Marques et al 2016). Recent studies have suggested the use of RNA interference as a promising alternative or complementary strategy for pest control and management (Asokan et al 2014;Kim et al 2015;Fishilevich et al 2016;Yu et al 2016;Ni et al 2017). …”
Section: Management Of Resistancementioning
confidence: 99%